2013
DOI: 10.1080/10962247.2013.801374
|View full text |Cite
|
Sign up to set email alerts
|

Indoor particulate matter in urban residences of Alexandria, Egypt

Abstract: Indoor particulate matter samples were collected in 17 homes in an urban area in Alexandria during the summer season. During air measurement in all selected homes, parallel outdoor air samples were taken in the balconies of the domestic residences. It was found that the mean indoor PM 2.5 and PM 10 (particulate matter with an aerodynamic diameter 2.5 and 10 m, respectively) concentrations were 53.5 AE 15.2 and 77.2 AE 15.1 µg/m 3 , respectively. The corresponding mean outdoor levels were 66.2 AE 16.5 and 123.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…The subjects of this study spent the majority of their day indoors; this, domestic sources reported previously (pets, mold, cooking, aerosol use) likely played a very important role in personal exposure [ 32 ]. Smoking inside the home and the use of carpets (in the house) are also significant domestic sources of PM 2.5 [ 32 , 42 , 43 ]. In this study, despite the fact that some relatives of some of the participants reported smoking in the home, passive smoking was not a significant source in the model of personal exposure to PM 2.5 or in the model for a decrease in PEF.…”
Section: Resultsmentioning
confidence: 99%
“…The subjects of this study spent the majority of their day indoors; this, domestic sources reported previously (pets, mold, cooking, aerosol use) likely played a very important role in personal exposure [ 32 ]. Smoking inside the home and the use of carpets (in the house) are also significant domestic sources of PM 2.5 [ 32 , 42 , 43 ]. In this study, despite the fact that some relatives of some of the participants reported smoking in the home, passive smoking was not a significant source in the model of personal exposure to PM 2.5 or in the model for a decrease in PEF.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a thorough chemical characterization of PM, which is composed of thousands of chemical species, is practically unfeasible. Up to now, most of the studies about indoor atmospheric PM were in fact focused on PM mass concentration only (mostly PM 2.5 : Abdel‐Salam, ; He et al., ; Massey et al., ; Meng et al., ; Yassin et al., ) or on individual PM components or groups of components, such as water‐soluble ions or/and elemental and organic carbon (EC, OC) or/and elements (Graney et al., ; Hasheminassab et al., ; Kulshrestha et al., ; Lazaridis et al., ; Molnar et al., , ; Na et al., ; Rivas et al., ). The widest ones among the above studies, although far from reaching a complete speciation of PM, include the determination of a very high number of components, microcomponents, and source tracers.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the increase of indoor fine PM concentration is mainly affected by outdoor traffic emissions, which contribute to a considerable amount of airborne fine particles in urban areas (Riley et al, 2002;Perez et al, 2010). When indoor sources are present, indoor PM concentrations can be higher than outdoor PM concentrations (Zhang et al, 2010;Abdel-Salam, 2012, 2013. Fine particles, in both indoor and outdoor air, were found to have the most serious effects on health, including increasing rates of cardiovascular and respiratory mortality and morbidity, as these are easily inhaled into the alveolar region (Heidi, 2000;Pope et al, 2002Pope et al, , 2009WHO, 2006).…”
Section: Introductionmentioning
confidence: 99%